FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUASAN PELANGGAN DI CLARION HOTEL & CONVENTION MAKASSAR - Nuraini Nuraini (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
This study aims: to determine whether factors such as pricing policies, promotion and support facilities effect on customer satisfaction and to identify the factors most dominant influence on customer satisfaction at the Clarion Hotel & Convention Makassar. This study used a multiple regression method. The research data used were obtained from interviews, documentation and questionnaires. The results of this study show that: 1) the pricing policy partially positive and significant impact on customer satisfaction at the Clarion Hotel & Convention Makassar, 2) promotion of partial positive and significant impact on customer satisfaction at the Clarion Hotel & Convention Makassar, 3) support facilities in partial positive and significant impact on customer satisfaction at the Clarion Hotel & Convention Makassar, and 4) the pricing policy, promotion and support facilities simultaneously positive and significant impact on customer satisfaction at the Clarion Hotel & Convention Makassar. And variable price policy is the variable most dominant influence on customer satisfaction at the Clarion Hotel & Convention Makassar.